Diagnosis of environmental impacts using the SAIA: A case study in the Brígida irrigation project, in the town of Orocó/PE, Brazil - Figueiredo, Roberto Tenorio; Santos, Vivianni Marques Leite dos; Ramos, Jorge Luis Cavalcanti (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2023)
Environmental impact assessment (EIA) is a decision-making tool and in many cases is a legal requirement in projects with activities potentially causing environmental degradation. In the case of agroecological projects, negative impacts are not allowed and an assessment is important to identify factors that distance them from the agroecological proposal. Based on the literature, the EIA, in general, is done with electronic spreadsheets, there is no software focused on the process. In view of this, the objective of this article was to carry out a diagnosis of environmental impacts in the Brígida Irrigation Project - Orocó/PE during the planting of different crops and animal husbandry, presenting a system to facilitate this task, named SAIA - Impact Assessment System Environmental, which can point out impacts that detract from an agroecological theme project. For this, after a survey on EIA techniques and agroecological projects, on the basis of scientific works and patents, the SAIA was validated in that Project, with questionnaires being applied with the participating family farming producers, to align the tool to the agroecological proposal. The diagnosis allowed us to conclude that there are negative impacts that keep the Project away from agroecology for all analyzed crops and creations. It is noteworthy that the number of impacts is not fixed for each type of crop, as it depends on how the steps are carried out. Furthermore, there was good acceptance of the tool, with suggestions, which were accepted, bringing SAIA closer to the reality of producers.